Toward Understanding CB[7]-Based Supramolecular Diels-Alder Catalysis - Berta, Dénes; Szabó, István; Scherman, Oren A.; Rosta, Edina (Frontiers in Chemistry, 2020)
Cucurbiturils (CBs) are robust and versatile macrocyclic compounds, often used as molecular hosts in complex supramolecular systems. In previous work, remarkable catalytic activity has been observed for asymmetric cycloadditions under very mild conditions. Herein, we investigate the nature of supramolecular catalysis using DFT calculations and QM/MM techniques. We discuss induced conformational changes, electrostatic shielding effects from the highly polar aqueous environment and cooperativity in hydrogen bonding of the substrates in explicit water using QM/MM simulation techniques. Our results show little specificity for the chosen molecules, suggesting an excellent opportunity to expand the scope for catalytic use of these supramolecular macrocyclic containers.